(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2011)
Hector Berlioz composed Cléopâtre to compete for 1829 Prix de Rome. He was so sure to win the prize that – setting a short Vieillard’s text to music having in mind Shakespeare’s Juliet monologue about sepulture – he allowed himself to indulge in formal experimentations perfectly coherent with his research about an ideal theater and the theme of memory, both developed in his later years. This is the reason why Cléopâtre displeased the jury but remains young Berlioz’s best achievement.